Hubungan Lama Paparan Bising terhadap Noise Induced Hearing Loss - Tengku Aida Fawziya Safa; Rano Aditomo; Renny Swasti Wijayanti; Joko Wahyu Wibowo (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Exposure to noise in industrial work environments can increase the risk of Noise-Induced Hearing Loss (NIHL) among workers. Prolonged exposure to continuous noise has the potential to cause hearing loss due to damage to the hair cells in the cochlea. This study employed an observational analytic method with a cross-sectional approach involving 36 employees of PT. Phapros Tbk. Data were collected via questionnaires and audiometric examinations, then analyzed using Spearman’s correlation test. The results showed that most respondents were exposed to moderate noise levels, and the majority had normal hearing. The Spearman test yielded a p-value of 0.079 with a correlation coefficient of 0.297, indicating no significant association between duration of noise exposure and hearing impairment.